Penentuan Arah Kiblat Menurut Sheikh Tahir Jalaluddin dalam Kitabnya Pati Kiraan Pada Menentukan Waktu Yang Lima dan Hala Kiblat dengan Logaritma: The Determination of Qiblah by Sheikh Tahir Jalaluddin in His Book Pati Kiraan Pada Menentukan Waktu Yang Lima dan Hala Kiblat dengan Logaritma - Mohammad Ikhsan, Siti Rahimah; Ahmad Zaki, Nurulhuda; Ali, Abdul Karim (Jurnal Fiqh, 2019)
Sheikh Tahir Jalaluddin is a Malay scholar who introduced the logarithmic method to determine the Qiblah. There are three logarithmic methods recorded in his book, Pati Kiraan. Sheikh Tahir mentions that the Qiblah calculation in the logarithmic method is relatively easier than the previous method of ‘ilm almiqat since the logarithmic method uses the ‘sistem persepuluhan’ (decimal system). Whereas, the ‘ilm al-miqat method uses the ‘sistem perenampulahan’ (sexagesimal system). Although the method for the determination of Qiblah using logarithm is easier, these three methods of Sheikh Tahir Jalaluddin have not yet been tested for their accuracy. Furthermore, previous studies have found that the methods are less accurate than the modern approach for determining the Qiblah. Thus, this study endeavors to analyze the accuracy of the three logarithmic methods in determining the direction of Qiblah. This study uses library resources for collecting the data and analyzes the data using comparative methodology. The results found that the calculation error in Sheikh Tahir’s logarithmic method is around one degree. The value is still can be accepted as it is an ijtihadi and ẓannī. The methods therefore can be used as a reference in determining the direction of Qiblah in Malaysia and it still can be benifited by Muslim astronomers to acknowledge Sheikh Tahir Jalaluddin’s pioneer services of modern methods in determining the direction of the Qiblah in Malaysia.